URBAN SPACE AND THE RIGHT TO THE CITY: DESPOILER EFFECT OF THE PROGRAMME JOAO PESSOA SUSTENTÁVEL IN THE COMMUNITY PORTO DO CAPIM-JOAO PESSOA-PB - Franca, Diego Pessoa Irineu de [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2024)
Contemporary cities are being reconfigured by the imperatives of capital. Jo & atilde;o Pessoa Sustentavel Programme (JPSP), financed by the Inter-American Development Bank (IDB), is an example of how the city social and spatial dynamic has been formatted by the hegemonic agents. This article reviews the unequal appropriation of the urban space of Jo & atilde;o Pessoa-PB, considering the contradictory interfaces between the infrastructure megaprojects and the peripheral populations' right to the city. In a methodological way, it was centered on secondary data survey, in the documental analysis, in the participative research, in the mapping creation, as well as in the field research, carried out pani passu with the megaprojects developments in the affected communities. Initially, the JPSP great magnitude is characterized, in the capitalist reproduction framework that focuses on some Latin American cities. Later, is emphasized the specificity of Joao Pessoa which is located on the scope of the Emergent and Sustainable Cities (ESCI) of BID. After that, the despoiler character of one of its subprojects is considered: The Sanhaua Ecologic Park, more specifically, starting from threat to Porto do Capim Communityl.
Keywords: Urban space; spoliation; right to the city